The Effect of Digital Competence on Improving Teacher Performance: A Case of Harapan Christian Vocational School in Rantepao - Agustinus Palimbong; Mesta Limbong; Witarsa Tambunan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The problem at SMK Kristen Harapan Rantepao is the low performance of teachers in learning. To improve teacher performance, it is necessary to analyze and prove the factors causing the low performance of the teacher. Many factors can affect teacher performance, but this study only focuses on examining "The Influence of Digital Competence on Teacher Performance at SMK Kristen Harapan Rantepao, North Toraja Regency". The purpose of this study was to analyze the effect of digital supervision and competence on teacher performance. The sample of this research is all teachers at the Christian Vocational School of Harapan Rantepao which were determined purposively involving 40 people. The method used in this research is multiple regression analysis. A simple linear regression analysis will analyze whether supervision affects teacher performance, whether digital competence affects teacher performance, and whether supervision and digital competence together affect teacher performance? The results of this study are expected to be a reference for schools to improve teacher performance through the implementation of supervision and improvement of digital competence.